Water-absorbing curing composite material suitable for high-water-content sludge and application of water-absorbing curing composite material

By using chemical waste materials such as calcium carbide slag, mineral powder, fly ash and other water-absorbing materials in high-water content sludge, the problem of low sludge curing strength is solved, efficient and economical sludge curing effect is achieved, and engineering costs are reduced.

CN119613018APending Publication Date: 2025-03-14SOUTHEAST UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411784075.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

When dealing with high moisture content sludge, the curing strength is low, the curing effect is not ideal, and increasing the amount of curing agent will lead to an increase in engineering cost.

Method used

The water-absorbent curing composite material consisting of calcium carbide slag, mineral powder, fly ash, sodium bentonite, carboxymethylcellulose sodium and hyperabsorbent resin is used to improve the solidified soil strength and long-term stability through synergistic action.

Benefits of technology

The curing strength of high-water content sludge is significantly improved, the curing time is shortened, the curing efficiency is improved, and carbon emissions is reduced, thus realizing the resource utilization of sludge.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613018A_ABST
    Figure CN119613018A_ABST
Patent Text Reader

Abstract

The invention relates to a water-absorbing and curing composite material suitable for high-water-content sludge and application thereof. The water-absorbing and curing composite material comprises the following raw material components in parts by weight: 40-65 parts of carbide slag, 10-30 parts of mineral powder, 10-25 parts of fly ash, 0.1-5 parts of sodium bentonite, 0.1-6 parts of sodium carboxymethyl cellulose and 0.01-1 part of super absorbent resin. Compared with the prior art, the curing material and the water absorbing material are compounded to cure the sludge, and the sludge is used as roadbed filler, so that the requirements of roadbed engineering can be met, and the problem of resource utilization of the sludge is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of geotechnical building materials and relates to a water-absorbing and solidifying composite material suitable for high-water content sludge and application thereof. Background Art

[0002] During the construction of engineering projects such as port, waterway and river dredging, a large amount of silt is often generated. Silt usually has the characteristics of high water content, high porosity, high compressibility, low bearing capacity and low permeability ("three highs and two lows"), and its engineering properties are poor, making it difficult to use directly in engineering.

[0003] At present, there are four main methods for disposing silt at home and abroad: land reclamation, physical dehydration, heat treatment, and solidification treatment. The land reclamation method is to blow the silt into the seaside cofferdam, treat it properly and then use it as foundation soil. The advantage of this method is that it can treat silt on a large scale. The disadvantages are high cost, long treatment cycle, and small scope of application. It is only applicable to silt generated in offshore areas; the physical dehydration method is to use physical methods to reduce the moisture content of silt. The commonly used physical dehydration method is natural drying. The advantage of this method is good economy and no other additional expenditure is required. The disadvantage is that it occupies a large area, has a long drying cycle, and the lower layer of silt is difficult to dehydrate and is easily affected by the weather. In addition, there is a mechanical dehydration method. The advantage of this method is that it occupies a small area and is not affected by natural conditions. The disadvantage is that the one-time investment is high, and the dehydrated silt needs secondary treatment; the heat treatment method is to directly convert the clay minerals in the silt into civil engineering materials by heating and other methods. The heat treatment method is divided into two forms: sintering and melting. Sintering is generally used to make bricks from silt, while melting is used to melt inorganic minerals in silt to make ceramsite and other materials. The advantage of the heat treatment method is that the treated silt can be sold, which has high economic value, but the disadvantage is that the treatment performance is limited; the solidification treatment method is to add solidification materials to the silt, so that the solidification materials and the water and clay in the silt produce a series of physical and chemical reactions, thereby improving its physical and mechanical properties, so that it can be directly used in engineering.

[0004] At present, the solidification treatment method generally uses chemical admixtures such as cement and lime to solidify the sludge. Many scholars have conducted research on this solidification treatment method, but most of these studies use inorganic composite materials to treat low-water content sludge (initial water content is less than 1 times the liquid limit). A few studies on high-water content sludge also have disadvantages such as low solidification strength and unsatisfactory solidification effect. However, in actual projects, the water content of dredged sludge is usually higher than the liquid limit. If you want to improve the strength of dredged sludge after solidification, you need to increase the amount of curing agent, which will increase the cost of the project.

[0005] Chinese patent application CN202210173658.7 discloses a sludge solidifying agent, a composite material and a preparation method thereof. The sludge solidifying agent includes the following components: 40-50 parts of fly ash, 10-20 parts of carbide slag, 5-10 parts of phosphogypsum, 4-6 parts of water glass, and several parts of water. The formula in this patent with fly ash, water glass and phosphogypsum as the main materials, although it has gelling properties to a certain extent, has obvious defects in solidifying high-water content sludge. First, the gelation reaction of water glass and alkali-activated fly ash can improve the strength of solidified sludge. However, the gel substances (hydrated calcium silicate and aluminum silicates) generated in the water glass activation system have a high porosity, and will shrink due to water loss in the later stage of the reaction, which is easy to cause cracking of the solidified body or a decrease in structural stability. Secondly, phosphogypsum is highly soluble in water, and the solidified body may have problems of secondary expansion or strength reduction in the later stage. In addition, this formula has a weak ability to adsorb free water, making it difficult to quickly reduce the moisture content in the sludge, resulting in prolonged curing time and low curing efficiency, especially when treating high-water-content sludge. These defects may lead to insufficient strength of the cured body, prolonged curing time and reduced durability, which is not conducive to application under complex working conditions. Summary of the invention

[0006] The purpose of the present invention is to provide a water-absorbing and solidifying composite material suitable for high-water content sludge and its application. When it is used to treat sludge, a roadbed filler that meets the requirements of roadbed engineering can be obtained, and the problem of resource utilization of sludge can be solved simultaneously.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] In the first aspect, the present invention provides a water-absorbing and solidifying composite material suitable for high-water content sludge, comprising the following raw material components in weight fractions: 40-65 parts of carbide slag, 10-30 parts of mineral powder, 10-25 parts of fly ash, 0.1-5 parts of sodium bentonite, 0.1-6 parts of sodium carboxymethyl cellulose, and 0.01-1 parts of super absorbent resin.

[0009] Furthermore, the carbide slag is high-calcium carbide slag, and the mass content of calcium oxide is higher than 70%.

[0010] Furthermore, the mineral powder is S95 grade mineral powder, and the mass proportion of the particle size less than 0.075 mm accounts for 4%.

[0011] Furthermore, in the fly ash, the proportion of particles with a diameter less than 0.075 mm is 4.5%, and the mass content of silicon oxide and aluminum oxide is greater than 80%.

[0012] Furthermore, the sodium bentonite is a white powdery solid, and the proportion of particles with a diameter less than 0.075 mm is 2%.

[0013] Furthermore, the pH of the sodium carboxymethyl cellulose is 6.8-8, the viscosity pH is 300 degrees-600 degrees, and the chloride content is less than 3%.

[0014] Furthermore, the super absorbent resin is a WHS-700C super absorbent resin, the proportion of particles smaller than 0.075 mm is 1%, the pH is 5.8-6.8, and the density is 0.58-0.68 g / cm 3 , the absorption of physiological saline is greater than 60g / g.

[0015] In a second aspect, the present invention provides a water-absorbing and solidifying composite material suitable for high-water content sludge, and its use as a curing agent in treating roadbed fillers.

[0016] Furthermore, when in use, the highly absorbent resin is first mixed with the sludge, stirred evenly and then allowed to stand, and then other components of the water-absorbing and curing composite material are added to convert the sludge into a roadbed filler.

[0017] Furthermore, the water content of the sludge is 1 times the liquid limit;

[0018] The blending amount of the water-absorbing and solidifying composite material is 10%-15% of the mass of the wet sludge.

[0019] The present invention utilizes the synergistic effect of the solid waste material component and the water-absorbing material component to improve the strength of the solidified soil and provide a strong guarantee for the long-term stability of the solidified soil. The specific principle is as follows.

[0020] The addition of carbide slag in the present invention can stimulate the reaction activity of fly ash and mineral powder on the one hand, and supplement Ca for the solidified soil system on the other hand. 2+ The two types of industrial solid wastes work synergistically with the active silicon and aluminum components in the soil to generate CASH gel and NASH gel, aluminum gel, network structure products formed by the polymerization of silicon-oxygen tetrahedron and aluminum-oxygen tetrahedron, etc. These reaction products can effectively cement soil particles and fill the pores of the solidified body, thereby improving the compactness of the solidified soil and increasing its strength.

[0021] The addition of mineral powder in the present invention provides aluminosilicate precursors for the alkali-induced reaction. Under the action of strong alkali, the Ca-O, Si-O and Al-O bonds are broken, releasing ions and monomers. The monomers interact with each other to form polymers, and low polymers are polymerized in a high calcium environment to form calcium silicate hydrate gel (CASH).

[0022] The addition of fly ash in the present invention forms a large amount of dissolved aluminum ions (Al 3+) and silicon ions (SiO2) in a solution and form a three-dimensional network structured polymer (NASH) through a condensation reaction. Since NASH has a stable three-dimensional structure, it can enhance the long-term durability of solidified sludge.

[0023] The WHS-700C super absorbent resin of the present invention is added. On the one hand, the WHS-700C super absorbent resin has excellent water absorption and water retention properties, and can absorb water in high-water content sludge, thereby improving the sludge strength. On the other hand, it can also fill the pores between soil particles and increase the cohesion between soil particles.

[0024] The addition of sodium bentonite in the present invention can absorb water on the one hand, and release Na on the other hand in high water content sludge. + , which can improve the water absorption capacity of the water-absorbent resin.

[0025] The addition of sodium carboxymethyl cellulose (CMC) in the present invention can provide Na for the high water content sludge solution. + On the one hand, it can create an ionic environment and on the other hand, it can absorb moisture and enhance the bonding force between soil particles.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] (1) The solidifying components used are composed of carbide slag, mineral powder, and fly ash. The solidifying materials are all industrial solid waste. Using these to replace traditional solidifying agents can significantly reduce carbon emissions.

[0028] (2) The water-absorbing component is composed of WHS-700C super absorbent resin, sodium bentonite, and sodium carboxymethyl cellulose (CMC), which can quickly reduce the free water content of high-water content sludge and synergistically improve the water absorption capacity of the water-absorbing material, which can significantly improve the solidification strength of high-water content sludge.

[0029] (3) Through the synergistic effect of the water-absorbing material components and the solid waste material components, on the one hand, the water-absorbing material can absorb water, thereby reducing the water content of the high-water content sludge. In addition, the water-absorbing material has a water retention function and can provide the water required for the hydration reaction of the solidified sludge in the later stage of solidification. On the other hand, the generation of hydration products in the later stage of the solidification material can also fill the pores generated by the water-absorbing material due to the release of water. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The present invention is a flow chart for the preparation and use of water-absorbing and solidifying composite materials suitable for high-water content sludge. DETAILED DESCRIPTION

[0031] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0032] In the following embodiments, the carbide slag used is high-calcium carbide slag, which has a light gray appearance and a calcium oxide content of more than 70%;

[0033] The mineral powder used is S95 grade mineral powder, which is off-white in appearance, and the proportion of its particle size less than 0.075mm accounts for 4%;

[0034] The fly ash used is a gray-black powder solid, and the proportion of particles with a diameter less than 0.075 mm is 4.5%, and the content of silicon oxide and aluminum oxide in the fly ash is greater than 80%;

[0035] The WHS-700C super absorbent resin used is a white granular solid, with a particle size of less than 0.075 mm accounting for 1%, a pH of 5.8-6.8, and a density of 0.58-0.68 g / cm 3 , the absorption of physiological saline is greater than 60g / g;

[0036] The used sodium carboxymethyl cellulose (CMC) is a light yellow powder, with a pH value of 6.8-8, a viscosity pH value of 300-600 degrees, and a chloride content of less than 3%.

[0037] The rest of the raw materials or processing techniques, unless otherwise specified, are conventional commercially available raw materials or conventional processing techniques in the art.

[0038] Example 1

[0039] This implementation case is an application of industrial solid waste in conjunction with a water-absorbing material curing agent to solidify high-water content sludge as road subgrade filling material.

[0040] The industrial solid waste synergistic water-absorbing material curing agent in this embodiment includes a curing material component and a water-absorbing material component, wherein the curing material component is composed of 60 parts of carbide slag, 22 parts of mineral powder and 11.9 parts of fly ash; the water-absorbing material component is composed of 0.1 parts of WHS-700C type super absorbent resin, 2 parts of sodium carboxymethyl cellulose (CMC) and 4 parts of sodium bentonite.

[0041] The research object is the sludge from a certain area of ​​Nantong. Its basic physical properties are shown in Table 1. The mass percentages of the functional components of the industrial solid waste synergistic water-absorbing material composite sludge solidifying agent are shown in Table 2.

[0042] Table 1 Basic physical indicators of Nantong sludge

[0043]

[0044] Table 2 Mass percentage of each functional component of industrial solid waste synergistic water-absorbing material composite sludge solidifying agent

[0045]

[0046] Take a certain mass of silt, the moisture content of which is 1 times the liquid limit. On the one hand, mix the WHS-700C super absorbent resin with the silt, stir evenly and let it stand for about 15 minutes, then add a curing agent according to about 12% of the wet soil mass of the silt, and use the static pressing method to make 3 cylindrical specimens of Φ50×100mm, the specimen type number is type 1; on the other hand, the silt without any curing agent and with a moisture content of 1 times the liquid limit is solidified by static pressing to make 3 cylindrical specimens of Φ50×100mm, the specimen type number is type 2. After demoulding, both are placed in a curing box with a humidity of 95% and a temperature of 20±2℃ for curing; after curing for 7 days, an unconfined compressive test is carried out to obtain the unconfined compressive strength of the specimen, see Table 3.

[0047] Table 3 Unconfined compressive strength of solidified sludge

[0048] Specimen type 1 2 3 average value Type 1 277.56KPa 290.32KPa 300.12KPa 289.33KPa Type 2 78.27KPa 76.83KPa 74.62KPa 76.57KPa

[0049] It can be seen from Table 3 that the compressive strength of the solidified sludge obtained after adding the solidifying agent is about 277-301 KPa, which is 400% higher than that without adding the solidifying agent.

[0050] Comparative Example 1

[0051] In order to better illustrate the technical effect of the industrial solid waste synergistic water-absorbing material soil solidifier in the present invention to solidify high-water content sludge, the present invention uses the solidifier component and carbide slag as a comparison. The specific comparison example is as follows:

[0052] The sludge selected as the research object of this comparative example is the sludge used in Example 1, and its basic physical property indicators are shown in Example 1.

[0053] The object of study of this comparative example is carbide slag, which is high-calcium carbide slag. The calcium oxide content of the carbide slag should be higher than 70%, which is the same as the carbide slag used in Example 1.

[0054] The preparation method of the sample in this comparative example 1 is as shown in Example 1. Similarly, the sample of industrial solid waste synergistically used as a water-absorbing material curing agent (i.e., the curing agent of Example 1) to solidify 1 times the liquid limit sludge is taken as Type 1, and the sample of calcium carbide slag to solidify 1 times the liquid limit sludge is taken as Type 2; after demolding, both are placed in a curing box with a humidity of 95% and a temperature of 20±2°C for curing; after curing for 7 days, an unconfined compressive test is carried out to obtain the unconfined compressive strength of the samples, see Table 4.

[0055] Table 4 Solidified sludge strength under different solidifying agents

[0056] Specimen type 1 2 3 average value Type 1 277.56KPa 290.32KPa 300.12KPa 289.33KPa Type 2 173.24KPa 170.55KPa 182.65KPa 175.48KPa

[0057] It can be seen from the above table that the 7d strength of the cured soil specimens of the embodiments of the present invention meets the requirements of the specification, indicating that the soil curing agent of the present invention has a good curing effect and can be used for roadbed filling.

[0058] Comparative Example 2:

[0059] Compared with Example 1, most of them are the same, except that the addition of sodium bentonite is omitted, the other two water-absorbing material components are adjusted in equal proportions, and the total mass content of the water-absorbing material components is kept unchanged.

[0060] The properties of the sludge used in this comparative example 2, the method for preparing the sample, the curing method and the age are the same as those in Example 1. Finally, the strength thereof is tested, and the results are shown in Table 5.

[0061] Table 5 Solidified sludge strength under comparative example 2

[0062] Specimen type 1 2 3 average value Comparative Example 2 240.23KPa 245.78KPa 236.68KPa 240.90KPa

[0063] It can be seen from the above table that the 7d strength of the solidified soil specimen of Comparative Example 2 is about 49 KPa lower than that of the Type 1 specimen in Example 1, indicating that the addition of sodium bentonite can improve the strength of solidified sludge.

[0064] Comparative Example 3:

[0065] Compared with Example 1, most of the contents are the same, except that the addition of CMC is omitted, the other two water-absorbing material components are adjusted in equal proportions, and the total mass content of the water-absorbing material components is kept unchanged.

[0066] The properties of the sludge used in this comparative example 3, the method for preparing the sample, the curing method and the age are the same as those in Example 1. Finally, its strength is tested, and the results are shown in Table 6.

[0067] Table 6 Solidified sludge strength under comparative example 3

[0068] Specimen type 1 2 3 average value Comparative Example 3 210.01KPa 212.35KPa 215.47KPa 212.59KPa

[0069] It can be seen from the above table that the 7d strength of the solidified soil specimen of Comparative Example 3 is about 72 KPa lower than that of the Type 1 specimen in Example 1, which is greater than the decrease in Comparative Example 2, indicating that CMC can improve the strength of solidified silt, and the improvement effect is higher than that of sodium bentonite.

[0070] Comparative Example 4:

[0071] Compared with Example 1, most of the contents are the same, except that the addition of the super absorbent resin is omitted, the other two absorbent material components are adjusted in equal proportions, and the total mass content of the absorbent material components is kept unchanged.

[0072] The properties of the sludge used in this comparative example 4, the method for preparing the sample, the curing method and the age are the same as those in Example 1. Finally, its strength is tested, and the results are shown in Table 7.

[0073] Table 7 Solidified sludge strength under comparative example 4

[0074] Specimen type 1 2 3 average value Comparative Example 4 225.49KPa 229.11KPa 230.26KPa 228.29KPa

[0075] It can be seen from the above table that the 7d strength of the solidified soil specimen of Comparative Example 4 is about 61 KPa lower than that of the Type 1 specimen in Example 1, which is greater than the decrease in Comparative Example 2 and less than the decrease in Comparative Example 3. This shows that the superabsorbent resin can improve the strength of solidified sludge, and the improvement effect is higher than that of sodium bentonite and lower than that of CMC.

[0076] Comparative Example 5:

[0077] Compared with Example 1, most of them are the same, except that the addition of fly ash is omitted, the other two solidifying material components are adjusted in equal proportions, and the total mass content of the solidifying material components is kept unchanged.

[0078] The properties of the sludge used in this comparative example 5, the method for preparing the sample, the curing method and the age are the same as those in Example 1. Finally, its strength is tested, and the results are shown in Table 8.

[0079] Table 8 Solidified sludge strength under comparative example 5

[0080] Specimen type 1 2 3 average value Comparative Example 5 236.2KPa 241.22KPa 230.82KPa 236.08KPa

[0081] It can be seen from the above table that the 7d strength of the solidified soil specimen of Comparative Example 5 is about 53 KPa lower than that of the Type 1 specimen in Example 1, indicating that although the addition of fly ash can improve the strength of solidified silt, the improvement in early strength is limited.

[0082] Comparative Example 6:

[0083] Compared with Example 1, most of them are the same, except that the addition of calcium carbide slag is omitted, and the other two solidifying material components are adjusted in equal proportions to keep the total mass content of the solidifying material components unchanged.

[0084] The properties of the sludge used in this comparative example 6, the method for preparing the sample, the curing method and the age are the same as those in Example 1. Finally, its strength is tested, and the results are shown in Table 9.

[0085] Table 9 Solidified sludge strength under comparative example 6

[0086] Specimen type 1 2 3 average value Comparative Example 6 205.00KPa 207.19KPa 203.80KPa 205.33KPa

[0087] It can be seen from the above table that the 7d strength of the solidified soil specimen of Comparative Example 6 is about 84KPa lower than that of the Type 1 specimen in Example 1, which is greater than the decrease in Comparative Example 5. This shows that carbide slag can improve the strength of solidified silt, and the improvement effect is higher than that of fly ash.

[0088] Comparative Example 7:

[0089] Compared with Example 1, most of them are the same, except that the addition of mineral powder is omitted, the other two solidifying material components are adjusted in equal proportions, and the total mass content of the solidifying material components is kept unchanged.

[0090] The properties of the sludge used in this comparative example 7, the method for preparing the sample, the curing method and the age are the same as those in Example 1. Finally, its strength is tested, and the results are shown in Table 10.

[0091] Table 10 Solidified sludge strength under comparative example 7

[0092] Specimen type 1 2 3 average value Comparative Example 7 212.85KPa 218.79KPa 209.85KPa 213.83KPa

[0093] It can be seen from the above table that the 7d strength of the solidified soil specimen of Comparative Example 7 is about 75KPa lower than that of the Type 1 specimen in Example 1, which is greater than the decrease in Comparative Example 5 and less than the decrease in Comparative Example 6. This shows that mineral powder can improve the strength of solidified silt, and the improvement effect is higher than that of fly ash and lower than that of calcium carbide slag.

[0094] Comparative Example 8:

[0095] Compared with Example 1, most of them are the same, except that the addition of sodium bentonite, sodium carboxymethyl cellulose, and WHS-700C super absorbent resin is omitted, and other curing material components are adjusted in equal proportions to keep the total mass content of the curing material components unchanged.

[0096] The properties of the sludge used in this comparative example 8, the method for preparing the sample, the curing method and the age are the same as those in Example 1. Finally, its strength is tested, and the results are shown in Table 11.

[0097] Table 11 Solidified sludge strength under comparative example 8

[0098] Specimen type 1 2 3 average value Comparative Example 8 182.00KPa 185.60KPa 192.33KPa 186.64KPa

[0099] It can be seen from the above table that the 7d strength of the solidified soil specimen of Comparative Example 8 is about 102 KPa lower than that of the Type 1 specimen in Example 1, which is greater than the decrease in Comparative Examples 2, 3 and 4. This shows that sodium bentonite, sodium carboxymethyl cellulose and WHS-700C super absorbent resin can improve the strength of solidified sludge, reflecting the necessity of the combination of these three materials.

[0100] Comparative Example 9:

[0101] Compared with Example 1, most of the above are the same, except that the order of adding the WHS-700C super absorbent resin is adjusted, that is, the curing agent is added first, and then the WHS-700C super absorbent resin is added. Others remain unchanged.

[0102] The properties of the sludge used in this comparative example 9, the sample preparation method, the curing method and the age are the same as those in Example 1. Finally, its strength is tested, and the results are shown in Table 12.

[0103] Table 12 Solidified sludge strength under comparative example 9

[0104] Specimen type 1 2 3 average value Comparative Example 9 260.54KPa 265.77KPa 268.99KPa 265.1KPa

[0105] It can be seen from the above table that the 7d strength of the solidified soil specimen of Comparative Example 9 is about 24 KPa lower than that of the Type 1 specimen in Example 1, indicating that the order of adding the WHS-700C super absorbent resin has an effect on the strength of the solidified sludge, reflecting the importance of the construction process.

[0106] According to the characteristics of silt, the present invention selects appropriate corresponding functional components from the perspectives of promoting hydration, coagulation and hardening of the curing agent, alkali excitation, and water conversion, and determines the optimal dosage ratio of each functional component through indoor experiments. The curing agent of the present invention interacts with clay particles, and the generated gel and hydrate crystals improve the strength of the silt; Ca(OH)2 generated by the reaction of calcium ions with water promotes the hardening reaction; the strong alkalinity of carbide slag promotes the alkali excitation reaction of mineral powder and fly ash to generate hydration products such as CASH and NASH; WHS-700C type superabsorbent resin and sodium bentonite and sodium carboxymethyl cellulose (CMC) (CMC) and other absorbent materials have water absorption and water retention, can convert a large amount of free water in the silt into hydration water and adsorbed water, and stably exist in the absorbent material, thereby increasing the connection between soil particles and improving the strength of the silt; the present invention has the advantages of easy availability of each functional component, small dosage, low cost, good effect, etc., and can be directly used as roadbed filler after mixing and curing with silt, realizing the resource utilization of silt.

[0107] In the absence of conflict, the above embodiments and features in the embodiments may be combined with each other.

[0108] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A water-absorbing and solidifying composite material suitable for high-water content sludge, characterized in that: The invention comprises the following raw material components in weight fractions: 40-65 parts of carbide slag, 10-30 parts of mineral powder, 10-25 parts of fly ash, 0.1-5 parts of sodium bentonite, 0.1-6 parts of sodium carboxymethyl cellulose and 0.01-1 parts of highly absorbent resin.

2. The water-absorbing and solidifying composite material suitable for high-water content sludge according to claim 1, characterized in that: The carbide slag is high-calcium carbide slag, and the calcium oxide mass content is higher than 70%.

3. The water-absorbing and solidifying composite material suitable for high-water content sludge according to claim 1, characterized in that: The mineral powder is S95 grade mineral powder, and the mass proportion of the particle size less than 0.075 mm accounts for 4%.

4. The water-absorbing and solidifying composite material suitable for high-water content sludge according to claim 1, characterized in that: In the fly ash, the proportion of particles with a diameter less than 0.075 mm is 4.5%, and the mass content of silicon oxide and aluminum oxide is greater than 80%.

5. The water-absorbing and solidifying composite material suitable for high-water content sludge according to claim 1, characterized in that: The sodium bentonite is a white powdery solid, and the proportion of particles with a diameter less than 0.075 mm is 2%.

6. The water-absorbing and solidifying composite material suitable for high-water content sludge according to claim 1, characterized in that: The pH value of the sodium carboxymethyl cellulose is 6.8-8, the viscosity pH value is 300-600 degrees, and the chloride content is less than 3%.

7. The water-absorbing and solidifying composite material suitable for high-water content sludge according to claim 1, characterized in that: The super absorbent resin is WHS-700C super absorbent resin, the proportion of particles smaller than 0.075 mm is 1%, the pH is 5.8-6.8, and the density is 0.58-0.68 g / cm 3 , the absorption of physiological saline is greater than 60g / g.

8. Use of the water-absorbing and solidifying composite material suitable for high-water content sludge as claimed in any one of claims 1 to 7 as a curing agent in treating roadbed fillers.

9. The use of the water-absorbing and solidifying composite material suitable for high-water content sludge according to claim 8, characterized in that: When in use, the super absorbent resin is first mixed with the silt, stirred evenly and then allowed to stand, and then other components of the water-absorbing and curing composite material are added to convert the silt into a road subgrade filler.

10. The use of the water-absorbing and solidifying composite material suitable for high-water content sludge according to claim 9, characterized in that: The moisture content of the sludge is 1 times the liquid limit; The amount of the water-absorbing and solidifying composite material added is 10%-15% of the mass of the sludge.

Citation Information

Patent Citations

  • Sludge curing agent, composite material and preparation method of composite material

    CN114573254A

  • Composite type soil water retention agent and preparation

    CN101463247A

  • Soil water ecological effectiveness control method

    CN101743790A

  • Water-absorbent resin plastic concrete and preparation method thereof

    CN111875316A

  • Soil stabilizer for roadbed filling

    CN113214835A